Optimization of Crude Fiber Content in Nata Produced from Watermelon Rind through Variations in Molasses and Mung Bean Sprout Broth - Cholili, Muhammad Ramadhan; Putri, Fifijihana Dewirukmana; Putri, Khansa Farahdilla Irfanindya; Putri, Natasya Kharisma; Lutfi, Achmad; Trimulyono, Guntur (Jurnal Pijar Mipa, 2025)
Nata is a fermented product made from cellulose and synthesized by Acetobacter xylinum, offering potential as a functional food rich in dietary fiber. This study aimed to evaluate the effect of varying volumes of molasses and mung bean sprout (Phaseolus radiatus L.) broth as sources of carbon and nitrogen on the crude fiber content of nata produced from watermelon (Citrullus lanatus) rind waste. Each fermentation medium had a total volume of 1000 mL and included the following treatments: N1 (5% molasses and 5% sprout broth), N2 (10% molasses and 10% sprout broth), N3 (15% molasses and 15% sprout broth), and N0 (control), which used coconut water, granulated sugar, and food grade urea. Fermentation was carried out under static conditions at room temperature for 10 days, and the resulting nata was analyzed for crude fiber content using the gravimetric method. The results showed that variations in the volumes of molasses and sprout broth significantly influenced the crude fiber content of nata (p < 0.05). The Duncan Multiple Range Test (DMRT) further confirmed statistically significant differences among treatments. Treatment N2 produced the highest crude fiber content (8.05 ± 0.02%), while the control (N0) yielded the lowest value (5.11 ± 0.01%). The absence of nata formation in N3 indicated substrate saturation and nutritional imbalance. These findings emphasize the importance of carbon and nitrogen balance in optimizing nata production from agroindustrial waste. Treatment N2 was identified as the most effective in enhancing both crude fiber content and overall nata quality.